2015
DOI: 10.4062/biomolther.2014.134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baicalin on Oral Pharmacokinetics of Caffeine in Rats

Abstract: Scutellaria baicalensis is one of the most widely used herbal medicines in East Asia. Because baicalein and baicalin are major components of this herb, it is important to understand the effects of these compounds on drug metabolizing enzymes, such as cytochrome P450 (CYP), for evaluating herb-drug interaction. The effects of baicalin and baicalein on activities of ethoxyresorufin O-deethylase (EROD), methoxyresorufin O-demethylase (MROD), benzyloxyresorufin O-debenzylase (BROD), p-nitrophenol hydroxylase and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…First, we optimized the liquid chromatography to achieve good chromatographic separation among the isomers, caffeine, and their internal standards. Secondly, we addressed the importance of HCOOH on signal intensity and matrix effects of the analytes, which has been largely ignored by the earlier reported assays (Choi, Bae, Park, Kwon, Jang, Zheng, Lee, Lee and Bae 2013, Noh, Nepal, Jeong, Kim, Um, Seo, Kang, Park, Kang, Jeong and Jeong 2015, Noh, Oh, Nepal, Jeong, Choi, Kang, Kang, Jeong and Jeong 2016). Thirdly, we utilized isotopic analogs as internal standards ( i.e ., CAF-d9 for CAF, PAR-d3 for PAR, THY, and THM).…”
Section: Resultsmentioning
confidence: 99%
“…First, we optimized the liquid chromatography to achieve good chromatographic separation among the isomers, caffeine, and their internal standards. Secondly, we addressed the importance of HCOOH on signal intensity and matrix effects of the analytes, which has been largely ignored by the earlier reported assays (Choi, Bae, Park, Kwon, Jang, Zheng, Lee, Lee and Bae 2013, Noh, Nepal, Jeong, Kim, Um, Seo, Kang, Park, Kang, Jeong and Jeong 2015, Noh, Oh, Nepal, Jeong, Choi, Kang, Kang, Jeong and Jeong 2016). Thirdly, we utilized isotopic analogs as internal standards ( i.e ., CAF-d9 for CAF, PAR-d3 for PAR, THY, and THM).…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that CYP 1A would be selectively inhibited by chrysin in vitro . Thereby, the effect of chrysin on caffeine pharmacokinetics were studied in vivo because caffeine is a well-known substrate for CYP 1A (Noh et al ., 2015). …”
Section: Resultsmentioning
confidence: 99%
“…By enrichment, the inhibitory effects of chrysin on specific CYP isozymes could be more selectively determined (Noh et al ., 2015). Dexamethasone and 3-methylcholanthrene suspended in corn oil were intraperitoneally given to rats at a dose of 50 mg/kg and 40 mg/kg for 3 consecutive days, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, Noh et al . [40] reported that, although baicalin inhibited CYP1A activity in rat liver microsomes in vitro , there was no difference between pharmacokinetics of caffeine and its metabolites ( i.e. , paraxanthine, theobromine, and theophylline), when caffeine was orally administered 8 h after single intragastric administration with baicalin (0.2 g/kg) in rats, because sufficient plasma concentration of baicalin for CYP inhibition could not be reached.…”
Section: Baicalin and Baicalein Induced In Vivo Drug Interactionmentioning
confidence: 99%